Pituitary Stalk Thickening: Causes and Consequences. The Children’s Memorial Health Institute Experience and Literature Review - Moszczyńska, Elżbieta; Kunecka, Karolina; Baszyńska-Wilk, Marta; Perek-Polnik, Marta; Majak, Dorota; Grajkowska, `Wiesława (Frontiers in Endocrinology, 2022)
Background: Pituitary stalk thickening (PST) is a rare abnormality in the pediatric population. Its etiology is heterogeneous. The aim of the study was to identify important clinical, radiological and endocrinological manifestations of patients with PST and follow the course of the disease. Materials and methods: It is a study conducted in 23 patients (13 boys) with PST with/without central diabetes insipidus (CDI) diagnosed between 1990 and 2020 at Children’s Memorial Health Institute (CMHI) in Warsaw, Poland. We analyzed demographic data, clinical signs and symptoms, radiological findings, tumor markers, hormonal results, treatment protocols and outcomes. Results: The median age at the diagnosis of PST was 9.68 years (IQR: 7.21-12.33). The median time from the onset of the symptoms to the diagnosis was 2.17 years (IQR: 1.12-3.54). The most common initially reported manifestations were polydipsia, polyuria and nocturia (82.6%); most of the patients (56.5%) also presented decreased growth velocity. Hormonal evaluation at the onset of PST revealed: CDI (91.3%), growth hormone deficiency (GHD) (56.5%), hyperprolactinemia (39%), central hypothyroidism (34.8%), adrenal insufficiency (9%), precocious puberty (8.7%). The majority of the patients were diagnosed with germinoma (seventeen patients – 73.9%, one of them with teratoma and germinoma). Langerhans cell histiocytosis (LCH) was identified in three patients (multisystem LCH in two patients, and unifocal LCH in one patient). A single case of atypical teratoid rhabdoid tumor, suspected low-grade glioma (LGG) and lymphocytic infundibuloneurohypophysitis (LINH). The overall survival rate during the observational period was 87.0%. Conclusions: The pituitary infundibulum presents a diagnostic imaging challenge because of its small size and protean spectrum of disease processes. Germinoma should be suspected in all children with PST, especially with CDI, even when neurological and ophthalmological symptoms are absent.